Flooding and poverty: Two interrelated social problems impacting rural development in Tsholotsho district of Matabeleland North province in Zimbabwe - Dube, Ernest (Jamba, 2018)
Flooding and poverty are the two social problems that have coexisted within the rural communities of Tsholotsho district. As a result, both problems have negatively affected and disrupted the everyday pattern of lives of people living in the district. This study sought to highlight how the two problems combine to impact human societies. The objectives that the study sought to fulfil were to establish the impact of flooding on the development of rural communities, to analyse how poverty manifests itself in rural communities, to analyse the relationship that exists between flooding and poverty and to suggest ways for dealing with the two problems. A qualitative research approach, using interviews and observations, was used to gather data from the research participants. The study findings were that flooding impeded development through shifting of human populations, destruction of crops, shelter and livestock. Floods also affected human capital through causing injuries to members of the community. Poverty manifested itself in three ways – as a development barrier, a vulnerability amplifier and a non-discriminatory agent. The study further found that a strong relationship exists between flooding and poverty because of the fact that flooding causes or worsens poverty, whereas poverty increases flood vulnerability. The study concluded that the poor need government assistance to reconstruct shelter destroyed by floods. Furthermore, programs aimed at improving livelihoods of the poor are an indispensable imperative. This study informs policymakers and offers a methodological significance to development and disaster practitioners. It also adds to the body of literature on flooding and poverty.